2016
DOI: 10.1002/arco.5118
|View full text |Cite
|
Sign up to set email alerts
|

New dates for earth mounds at Weipa, North Queensland, Australia

Abstract: This paper reports new radiocarbon determinations for late Holocene occupation in the Weipa region of Far North Queensland, Australia. Earth mounds along the margins of small wetlands and freshwater creeks developed mainly after 2200 years ago, but are concentrated within the past 500 years. Their establishment appears to be associated with changing environmental conditions and a regional increase in the availability of permanent water sources around 2200 and 500 years ago. These results have implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…In an intensive study of four shell matrix sites located at the Wathayn outstation, they determined a high degree of variability existed between shell matrix sites, including hiatus periods in the formation of some mound sites. An expanded program of research focused on shell mound features followed, and sought to understand the temporal and spatial variability of a large number of sites at one locality, encompassing both shell matrix deposits (Fanning et al 2018;Holdaway et al 2017) and earth mounds (Brockwell et al 2017). This required a major program of field sampling to obtain stratigraphic profiles, column samples and radiocarbon determinations from 70 shell matrix features within a study area with at least 158 identified sites and some 212 radiocarbon determinations (Holdaway et al 2017).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In an intensive study of four shell matrix sites located at the Wathayn outstation, they determined a high degree of variability existed between shell matrix sites, including hiatus periods in the formation of some mound sites. An expanded program of research focused on shell mound features followed, and sought to understand the temporal and spatial variability of a large number of sites at one locality, encompassing both shell matrix deposits (Fanning et al 2018;Holdaway et al 2017) and earth mounds (Brockwell et al 2017). This required a major program of field sampling to obtain stratigraphic profiles, column samples and radiocarbon determinations from 70 shell matrix features within a study area with at least 158 identified sites and some 212 radiocarbon determinations (Holdaway et al 2017).…”
Section: Previous Researchmentioning
confidence: 99%
“…Although undertaken as a cultural heritage management project, this study contributes new datasets relevant to understanding late Holocene settlement patterns, economies and occupation chronologies on the Weipa Peninsula. Mandjungaar is approximately mid-way between two other intensively studied areas, the well-known Kwamter mound (Bailey 1977;Stone 1992Stone , 1995Wright 1971), as well as large mound complexes near Wathayn and Ndhinggwulung (Figure 1), that have been the focus of a recent and ongoing major research program (Brockwell et al 2017;Fanning et al 2018;Holdaway et al 2017;Shiner et al 2013). This paper reports on the research design and results of work at Mandjungaar, before considering these in relation to other work undertaken on the Weipa Peninsula, and across the Albatross Bay catchment more generally.…”
Section: Introductionmentioning
confidence: 98%
“…The mounds are described as low‐lying and easily overlooked (Brockwell et al . : 129). Photographs of the mounds (refer to Brockwell et al .…”
Section: Introductionmentioning
confidence: 98%
“…Bourke ; Brockwell , , , , ; Brockwell et al . ; Burns ; Cribb , ; Meehan , ; Meehan et al . ; Shiner & Morrison ; Peterson ; Woodroffe et al .…”
Section: Introductionunclassified
See 1 more Smart Citation